Cash Waqf Linked Sukuk (CWLS) Dalam Kajian Fatwa DSN MUI Di Indonesia - Puspitasari, Neneng; Khotimah, Khusnul (Tasyri' : Journal of Islamic Law, 2022)
Cash waqf or it also called by Cash Waqf Linked Sukuk (CWLS) is one of the alternative of taking poverty that has implemented in some islamic nations. Cash waqf has opened the unique opportunity for creating an investment religious field, education and sosial attendance. According to the calculation of BWI, the potential of Cash Waqf in Indonesia has achieved at least 180 billions in a year. This study is a research of normative law (doctrinal), which is used library research and juridical normative approach. This research could be concluded that Cahs Waqf Linked Sukuk (CWLS) becomes an alternative way in repairing economy field in Indonesia. In explaining instructions of DSN MUI, the rules of CWLS is written or decided in the instructions of DSN-MUI No. 131/X/2019 about Waqf Sukuk and the instructions of DSN-MUI No. 137/XI/2020 about Sukuk.